PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X SMKN 1 MANDAU TP. 2013 / 2014 - Ekarikardo '; Nahor Murani Hutapea Nahor Murani Hutapea; Sehatta Saragih Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to improve the learning process and improve learning outcomes class X learners of SMKN Negeri 1 Mandau by applying cooperative learning model TPS . The subjects were learners in class X which consisted of 4 women and 30 men with heterogeneous academic ability. This research is a class act with two cycles . Each cycle has four stages : planning, implementation, observation and reflection . Data collection instrument in this study is the observation sheet activities teachers and learners, as well as the achievement test. Sheets were analyzed qualitatively descriptive narrative, while the achievement test were analyzed by descriptive statistical study by analyzing the development of the individual and group values, KKM achievement analysis, and analysis of the success of the action. Results of research on the observation sheet shows the activity of teachers and learners have done well and according to plan after the action . Improvements in the learning process of students and increase the number of learners who achieve KKM at the end of each cycle UH compared to the number of learners who achieve a score of KKM on base score. At the base score only 35,29% of learners who reach KKM , the UH I increased to 58,82% and the UH II also increased to 73,52% . The results of this study indicate that the application of cooperative learning model TPS can improve the learning process and improve learning outcomes class X learners of SMK Negeri 1 Mandau in the second semester of the academic year 2013/2014. Keywords: Mathematics Learning Outcomes, Cooperative Learning, Think Pair Share (TPS), Classroom Action Research .